Transmission of faith through the Internet - Rodríguez Olaizola, José María (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2017)
This is a reflection about transmission of faith through the Internet. The author writes about different evangelization models, among them: adaptation, innovation, networking, and the dynamisms of information through the Internet, among them: content dispersal, the difficulty for depth, the constant demand of content actualization and novelty. At last he suggests some practical questions that should be taken into account in new projects: design, balance among technical skills and religious contents.
Keywords: Evangelization models; Internet; dynamisms of information.